Is neuron-specific enolase useful for diagnosing malignant pleural effusions? evidence from a validation study and meta-analysis - Zhu, Jing; Feng, Mei; Liang, Liqun; Zeng, Ni; Wan, Chun; Yang, Ting; Shen, Yongchun; Wen, Fuqiang (BMC cancer, 2017)
Background Neuron-Specific enolase (NSE) has been used as a typical tumor marker and shows a potential to diagnose malignant pleural effusion (MPE). The ability of NSE in diagnosing MPE has been investigated in many studies, but with inconsistent conclusions. This study sought to investigate the diagnostic accuracy of NSE for MPE through a clinical study and together with a meta-analysis. Methods Pleural effusion samples from 136 patients with MPE and 102 patients with benign pleural effusion (BPE) were collected, and NSE levels were measured by electrochemiluminescence immunoassay. Receiver operating characteristic (ROC) curve analysis was performed to assess the ability of NSE to differentiate MPE from BPE. Literature search was conducted to identify suitable publications, data were extracted and diagnostic indexes including sensitivity, specificity, positive/negative likelihood ratio (PLR/NLR), and diagnostic odds ratio (DOR) were pooled. Summary ROC curve was generated to determine the overall diagnostic accuracy of NSE for MPE. Results Levels of NSE were significantly increased in pleural effusion from patients with MPE than that from BPE (18.53 ± 27.30 vs. 6.41 ± 6.95 ng/ml, p < 0.001). With a cut-off value of 8.92 ng/ml, pleural NSE had a sensitivity of 59.56% and a specificity of 83.33% in diagnosing MPE. A total of 14 studies with 1896 subjects were included for meta-analysis. The diagnostic parameters of NSE were listed as follows: sensitivity, 0.53 (95% CI: 0.38–0.67); specificity, 0.85 (95% CI: 0.75–0.91); PLR, 3.54 (95% CI: 2.33–5.39); NLR, 0.56 (95% CI: 0.42–0.73); and DOR, 6.39 (95% CI: 3.72–10.96). The area under the summary ROC curve was 0.78. Conclusions The role of pleural NSE measurement in diagnosing MPE is limited and with a low sensitivity. The clinical utility of NSE assay should be combined with the results of other tumor markers examination and the detail clinical information of patient. Further studies are needed to confirm the role of NSE in diagnosing MPE.